Paveldo industrija Lietuvoje - Vaitkuvienė, Agnė (Lietuvos istorijos studijos, 2006)
The article aims to review the situation of the heritage industry in Lithuania after 1990. The article consists of the sections on the logic of terms and theoretical contexts, the study of the heritage boom and the rise of economic value in heritage protection, and the identification of heritage producers and users. The section on the logic of terms gives definitions and explanations of such concepts as "heritage," "heritage industry," and at the same time, theoretical contexts are clarified. The study of the heritage boom and the rise of economic value in cultural heritage protection analyzes the socio-cultural situation of the end of the XXth century, changes in the conception of cultural heritage protection from a conservation position to cultural heritage management. In this section, the rise of the heritage industry under the influence of the heritage boom is identified and described. At the same time, connections of the heritage industry with changes in historical sense are defined. The study of heritage industry producers and users describes them according to three fields: culture, politics, and business. It indicates that the heritage industry is most frequent in show business and the service industry. The conclusions indicate that the origin of the heritage industry in Lithuania dates from 1998. It is closely connected with the rise of economic and purchasing power of the population, and then people could spend more time and money on leisure and entertainment, including cultural heritage. At the same time, changes in historical sense are observed. But all those changes did not affect the situation of Lithuanian heritage protection. The heritage industry in Lithuania occurred not in the contexts of cultural heritage management but in leisure and entertainment marketing.